Analysis of Local Wisdom as Environmental Conservation Strategy in Indonesia - Astri Hasbiah (SAMPURASUN, 2015)
Environmental problems as a result of unsustainable development require holistic solution to be solved. One of the solutions is the reimplementation of local wisdom. In the past, people lived in harmony with the environment and almost all ethnic groups in Indonesia have the wisdom to preserve and manage the environment inherited by their ancestors. Local wisdom is invaluable tradition that has influenced people’s attitude and behaviour towards nature. However, this wisdom is abandoned by modern developments. This study aims to analyse the reimplementation of local wisdom as an environmental conservation strategy. Difficulties in learning and using local wisdom practiced in the past are encountered in the reimplementation process. This is due to unavailability of local wisdom official records. Another difficulty is society’s unwillingness to re-implement local wisdom. Local wisdom is considered as outdated by many people. Reimplementation of local wisdom can be conducted through systematic approach in education system, integrated socio cultural approach and consistent government development policies. The re-implementation of local wisdom should be adapted to current times. It should not simply adopt local wisdom in the past as it was because it will not suitable with the present time. Renewal of existing local wisdom can be used by the government to create sustainable development. Environmental conservation should be conducted by considering local situation and condition as Indonesia has a very diverse population and environmental conditions. Keywords: environmental conservation; local wisdom.